The Effectiveness Of The Official Website As A Disclosure Of Corporate Social Responsibility : Efektivitas Official Website Sebagai Pengungkapan Corporate Social Responsibility - Dwi Prihandoko; Hadiah Fitriyah (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to know the effectiveness of the official website at Bank Mandiri Syariah as a disclosure of Corporate Social Responsibility. This type of research is qualitative. The data source of this study was data from CSR reports from the official website of Syariah Mandiri Bankin June 2020. Researchers used documentation data collection techniques. Data were analyzed using Moleong theory (2016). The results of this study include, on its official website, Bank Mandiri Syariah has sought to address all issues related to CSR. The existence of a special CSR menu on the main page of the page shows that Bank Mandiri Syariah pays attention to the importance of CSR information to the public (high hierarchy). The location of CSR information carried out by Bank Mandiri Syariah is widely located or the position of information is conveyed on the website compared to media outside the website. The use of expositive information sources in the form of text, images, photographs and graphics alone shows that this page is still one-way (unidirectional), and the Bank Mandiri Syariah Website does not provide adequate feedback as a medium of interaction and dialogue with different publics.